Advanced display technology next generation self-emitting displays - Kang, In Byeong; Han, Chang Wook; Jeong, Jae Kyeong (Singapore Springer, 2021)
This book provides a comprehensive and up-to-date guide to the AMOLED technologies and applications which have become industry standard in a range of devices, from small mobile displays to large televisions. Unlike other books on the topic, which cover the fundamentals, materials, processing, and manufacturing of OLEDs, this one-stop book discusses the core components, such as TFT backplanes, OLED materials and devices, and driving schematics together in one volume with chapters written by experts from leading international companies in the field of OLED materials and OLED TVs. It also examines emerging areas, such as micro-LEDs, displays using quantum dots, and AR & VR displays. Presenting the latest research trends as well as the basic principles of each topic, this book is intended for undergraduate and postgraduate students taking display-related courses, new researchers, and engineers in related fields.
Electronic reproduction
Keywords: Information display systems; Electronic books